Technology Blueprint Walk Care Rehab Supply / Nuramirah Mohd Ali - Mohd Ali, Nuramirah (2020)
Walk Care Rehab Supply is a partnership business that run based on the product produce that are usually use by disability people or people that have problem in walking around Johor Bahru, Johor . This business allocated at No.71, Jalan Bakawali, Taman Johor Jaya, 81100, Johor Bahru, Johor and it is near to the Hospital Sultan Ismail, Johor Bahru, Johor. This company provide equipment or product for disability people or people that need a product to support them for walking. The signature product of this company is Zass stick, a smart blind stick. This product is the first and only smart blind stick in the Malaysia’s market. This smart blind stick is create to solve the problem faced by blind and visually impaired people. Besides that, our company also provided other rehabilitee’ equipment such as electronic wheelchair, adjustable crutches and multifunction rollators. The concept for this business is producing a modern and comfortable equipment for the customer to walk that suit with our trade mark which is “walking is not a problem”.